Socially foraging bats discriminate between group members based on search-phase echolocation calls. (13th June 2020) - Kohles, Jenna E; Carter, Gerald G; Page, Rachel A; Dechmann, Dina K N
Abstract: Animals have evolved diverse strategies to use social information for increasing foraging success and efficiency. Echolocating bats, for example, can eavesdrop on bats foraging nearby because they shift from search-phase calls to feeding buzzes when they detect prey. Feeding buzzes can directly convey information about prey presence, but it is unknown whether search-phase calls also convey social information. Here, we investigated whether search-phase echolocation calls, distinct calls produced by some bat species to scan large open areas for prey, can additionally convey individual identity. We tested this in Molossus molossus, a neotropical insectivorous bat that forages with group members, presumably to find ephemeral insect swarms more efficiently. We caught M. molossus from six different social groups and recorded their search-phase calls during a standardized release procedure, then recaptured and tested 19 marked bats with habituation–dishabituation playback experiments. We showed that they can discriminate between group members based on search-phase calls, and our statistical analysis of call parameters supported the presence of individual signatures in search-phase calls. Individual discrimination is a prerequisite of individual recognition, which may allow M. molossus to maintain contact with group members while foraging without using specialized signals for communication. Abstract : Bats produce echolocation calls while searching the night sky to detect prey. We show that these calls also convey information about an individual's identity. Bats that forage socially with group members could discriminate between these individuals by listening to the echolocation calls they produce while foraging. Socially foraging bats rely on many modes of sharing information to exploit prey that is unpredictable and hard to find.